Sparen in der "Nullzinsphase". Privatanleger und der Kapitalmarkt in Deutschland im Ersten Weltkrieg - Gerd Hardach (IBF - Institut für Bank- und Finanzgeschichte, 2017)
Saving in the "Zero Interest Period". Private Investors and the Capital Market in Germany in the First World War: This paper offers a look back at the period of zero interest and even negative interest during the First World War. In contrast to the current period of low interest rates, during the war there was an illusion of interest: while savers did receive nominal interest on their deposits, however, the savings deposits lost value due to the war inflation such that it was effectively negative interest. Even at the end of the war only very few savers were aware that they had experienced a period of declining interest. Rather, they assumed that the purchasing power of the mark and the exchange rate would soon settle down at the pre-war level. The full scope of the dilemma for private investors during the zero interest period became apparent only in the post-war inflation. Although various options between inflation and deflation were still discussed during the revolution and at the beginning of the Weimar Republic, the monetary and fiscal path subsequently taken resulted in the uncontrolled inflation that had significantly greater effects on private investors and the capital market than the war inflation that directly preceded it.
Keywords: E43; E58; G21; N24; N34; 330